Upland paddy and blackgram strip cropping technology for enhanced productivity in Eastern Ghats of Odisha, India - Praveen Jakhar; P.P. Adhikary; B.S. Naik; Hombegowda H.C.; M. Madhu (Annals of Agricultural Research, 2022)
A field experiment was carried out during the rainy seasons (July-October) of 2011, 2012 and 2013 at Koraput, Odisha, to assess the performance of upland paddy [Oryza sativa L.] and blackgram (Phaseolus mungo L.) based strip cropping in ratios 6:4, 8:4, 10:4 and 12:4. The experiment was laid out in 3 replications on sloping land in a randomized block design. Among the tested ratios, strip cropping of 10 rows of upland paddy (DSR) with 4 rows of blackgram (BG) steadily gave higher paddy equivalent yield (DSREY). In percentage terms, it was 9.3, 14.2 and 10.2% higher than sole DSR. Analysis of 3 years’ data of DSREY indicates an average yield of 1330 kg/ha with an increase of 13.7 and 6.1% over 8:4 and 10:4 ratios, respectively. The maximum net returns of Rs 11,511 per ha were accrued from 10:4 DSR ratio, which was 28.7% higher than the net returns from sole DSR cultivation. The ratio also recorded highest benefit cost ratio (1.90). The superiority of strip ratio 10:4 was also reflected in the monetary advantage index and income-equivalent ratio, registering maximum values of 1750 and 2.50, respectively. Maximum value of land-equivalent ratio (1.18) was estimated in 10:4 ratio, indicating 18% area advantage over sole cropping. All the strip cropping systems were advantageous than sole planting systems as maximum values of KDSR and KBG, 2.12 and 1.28 respectively were obtained from 10:4 strip ratio, pointing greater advantage with highest K values (2.70).